Evaluation of a midwife-led, hospital based vaccination service for pregnant women. Issue 1 (2nd January 2021) - Skirrow, Helen; Holder, Beth; Meinel, Alison; Narh, Evelyn; Donaldson, Beverly; Bosanquet, Anna; Barnett, Sara; Kampmann, Beate
ABSTRACT: Background : Vaccines against whooping cough (pertussis) and seasonal-influenza are recommended for pregnant women in England. Uptake however varies regionally and by ethnicity. Pregnant women are traditionally vaccinated in primary care, though some hospitals now offer vaccines through antenatal clinics. This mixed-methods evaluation describes the demographic characteristics of women seen in a hospital midwife-led antenatal vaccine clinic and explores vaccine decision making. Methods : Descriptive statistics of women seen in a London hospital's midwife-led vaccine clinic were generated from electronic routine maternity records, including data on ethnicity, parity, age and deprivation indices. Reasons for vaccine decline given by women to midwives were categorized by themes. Qualitative interviews of women seen in the clinic were also undertaken. Results : Between 1st April 2017 and 31st March 2018 the vaccine clinic saw 1501 pregnant women. Of these, 83% received pertussis vaccine and (during flu season) 51% received influenza vaccine, from the clinic. Fewer Black Afro-Caribbean women seen by the clinic were vaccinated, compared to other ethnicities with only 68% receiving pertussis and 34% flu vaccines respectively ( p < .05). Among all women delivering at the hospital over the year, 42%, (1334/3147) were vaccinated by the clinic. Qualitative interviews found that reassurance from healthcare professionals, particularly midwives, was the most important factor influencing maternal vaccine decisions. Conclusions : Midwife-led hospital clinics can offer an effective alternative to primary care provision for vaccines in pregnancy. Consistent with previous work, vaccine uptake varied by ethnicity. Midwives play a key role in the provision of vaccine services and influence women's vaccine decisions.